2011
DOI: 10.1093/infdis/jir625
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Burden and Consequences of Pregnancy-Associated Malaria in the Democratic Republic of the Congo

Abstract: Background. Pregnancy-associated malaria (PAM) produces poor birth outcomes, but its prevalence is commonly estimated in convenience samples.Methods. We assessed the prevalence of malaria using real-time polymerase chain reaction (PCR) and estimated the consequences of infection on birth outcomes, using specimens from a nationally representative sample of 4570 women of childbearing age (WOCBA) . By contrast, P malariae was less common in pregnant (0.6%) compared with nonpregnant women (2.7%, PR 0.23 [0.09-0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…infection (peripheral parasitaemia detected by Plasmodium spp. slide positivity [ 8 , 19 , 20 ] or by PCR [ 21 ]) and parasite density[ 8 , 19 , 20 ] are higher during pregnancy. Similarly, the results of the present study show that the probability of malaria parasite detection in adult female chimpanzees also increases during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…infection (peripheral parasitaemia detected by Plasmodium spp. slide positivity [ 8 , 19 , 20 ] or by PCR [ 21 ]) and parasite density[ 8 , 19 , 20 ] are higher during pregnancy. Similarly, the results of the present study show that the probability of malaria parasite detection in adult female chimpanzees also increases during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In several studies in Africa and Asia, the prevalence of malarial parasitemia was found to be higher among pregnant females than among nonpregnant females 15 to 45 years of age. 18,37,38 P. falciparum is the only species associated with placental sequestration, which is believed to be the cause of many of the manifestations of P. falciparum disease during pregnancy. Many studies have shown decreasing susceptibility to malaria with increasing parity, 37-39 probably as a result of acquisition of immunity to parasites expressing pregnancy-specific variant surface antigens.…”
Section: Pregnancy and Susceptibility To Infectionmentioning
confidence: 99%
“…McGregor found the prevalence of malarial parasitemia in females aged 15–45 years to be significantly higher in pregnant than in nonpregnant women in their surveys from 1961 to 1975 in rural Gambia [25]. A slightly higher prevalence of parasitemia in pregnant than nonpregnant women of childbearing age (36.6% versus 28.8%, PR 1.27 [1.05–1.53]) was found in the Congo using DNA-based methods [26]. Women in their third trimester were at highest risk for clinical malaria in some [27] but not all studies [28].…”
Section: Malariamentioning
confidence: 99%